Martes americana Baker 1899 - Morrone, Juan J.; Acosta, Roxana (Zenodo, 2006)
S. americana (Baker, 1899) Hystrichopsylla americana Baker, 1899: 37. Stenoponia wetmorei Chapin, 1919: 52. Stenoponia americana Jordan, 1937:285. Distribution. Canada, USA, and Mexico. Hosts. Blarina brevicauda, B. carolinensis , and Sorex cinereus. Other hosts. Didelphimorphia: Didelphis virginiana. Insectivora (Talpidae): Scalopus aquaticus. Rodentia: Clethrionomys gapperi, Microtus ochrogaster, M. o. minor, M. pennsylvanicus, M. pinetorum, M. richardsoni arviculoides, Microtus sp., Peromyscus gossypinus, P. leucopus , and P. l. noveboracensis (Wilson, 1957; Benton & Kelly, 1975; Hopkins & Rothschild, 1962; McCay, 2001; SalcedaSánchez & Hastriter, 2006). Published as part of Morrone, Juan J. & Acosta, Roxana, 2006, A synopsis of the fleas (Insecta: Siphonaptera) parasitizing New World species of Soricidae (Mammalia: Insectivora), pp. 1-30 in Zootaxa 1354 on page 17, DOI: 10.5281/zenodo.273605